2018
DOI: 10.1155/2018/9070341
|View full text |Cite
|
Sign up to set email alerts
|

Irisin Exerts Neuroprotective Effects on Cultured Neurons by Regulating Astrocytes

Abstract: Neurons suffer detrimental effects from β-amyloid toxicity in Alzheimer's disease. The exercise hormone, irisin, is found to induce a neuroprotective gene program and facilitates the beneficial effects on cognitive function. But no effort is made to test its direct protective effects on neurons against the Aβ-induced cell toxicity so far. In the present study, we investigated whether irisin could protect neurons against Aβ- (25–35) induced cell damage and explored the possible underlying mechanisms. Primary ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 23 publications
0
38
0
Order By: Relevance
“…Dameni et al (2018) carried out their study in a chronic constriction injury model in male rats and found that acute administration of irisin increased pain threshold; however, irisin could not prevent the decline in the number of neurons [ 105 ]. Wang et al (2018) reported on the basis of their study in primary cell cultures of astrocytes and neurons that a pretreatment of astrocyte-conditioned medium with irisin for about 12 h protected neurons from the toxicity of amyloid-β [ 106 ]. Irisin could also attenuate the release of IL-6 and IL-1β from cultured astrocytes and reduced expression of COX-2 and phosphorylation of AKT [ 106 ].…”
Section: The Role Of Exercise In Neurological Diseases and Involvementioning
confidence: 99%
See 3 more Smart Citations
“…Dameni et al (2018) carried out their study in a chronic constriction injury model in male rats and found that acute administration of irisin increased pain threshold; however, irisin could not prevent the decline in the number of neurons [ 105 ]. Wang et al (2018) reported on the basis of their study in primary cell cultures of astrocytes and neurons that a pretreatment of astrocyte-conditioned medium with irisin for about 12 h protected neurons from the toxicity of amyloid-β [ 106 ]. Irisin could also attenuate the release of IL-6 and IL-1β from cultured astrocytes and reduced expression of COX-2 and phosphorylation of AKT [ 106 ].…”
Section: The Role Of Exercise In Neurological Diseases and Involvementioning
confidence: 99%
“…Wang et al (2018) reported on the basis of their study in primary cell cultures of astrocytes and neurons that a pretreatment of astrocyte-conditioned medium with irisin for about 12 h protected neurons from the toxicity of amyloid-β [ 106 ]. Irisin could also attenuate the release of IL-6 and IL-1β from cultured astrocytes and reduced expression of COX-2 and phosphorylation of AKT [ 106 ]. In addition, irisin could decrease NFκB activation of astrocytes exposed to amyloid-β by preventing phosphorylation and loss of IκBα [ 106 ].…”
Section: The Role Of Exercise In Neurological Diseases and Involvementioning
confidence: 99%
See 2 more Smart Citations
“…In a middle cerebral artery occlusion mouse model, irisin was reported to protect against cerebral ischemia-induced neuronal injury by reducing oxidative stress, suppress inflammation by reducing plasma TNFα and IL-6, inhibit the activation of Iba1 + microglia, and infiltrate MPO-1 + monocytes [ 25 ]. Irisin inhibits not only microglial activation but also NF-κB activation in cultured astrocytes, thereby reducing downstream COX-2 expression and releasing IL-6 and IL-1β [ 26 ]. Another study demonstrated its neuroprotective effect in cerebral ischemia/reperfusion injury by irisin-induced reduction in the activation of apoptosis and TNFα and IL-1β expression in brain tissue [ 27 ].…”
Section: Introductionmentioning
confidence: 99%